Phosphathiahelicenes: Synthesis and Uses in Enantioselective Gold Catalysis. Issue 39 (11th August 2014) - Aillard, Paul; Voituriez, Arnaud; Dova, Davide; Cauteruccio, Silvia; Licandro, Emanuela; Marinetti, Angela
Abstract Enantiomerically pure thiahelicenes displaying a terminal phosphole unit and a stereogenic phosphorus center have been prepared by oxidative photocyclization of a diaryl‐olefin precursor. Starting from one of these phosphathiahelicene oxides, the corresponding trivalent phosphine–AuI complex is obtained with complete diastereoselectivity. It affords a new, excellent precatalyst for the enantioselective cycloisomerization of N‐tethered enynes (up to 96 % ee).